2015
DOI: 10.1111/jocd.12203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the severity and triggering factors of sensitive scalp in Chinese females

Abstract: Questionnaires with more dimensions and details such as 10Q and 3S should be used for the diagnosis, prognosis, and treatment monitoring on sensitive scalp in Chinese female.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 21 publications
1
24
0
1
Order By: Relevance
“…A total of 62 healthy women aged between 19 and 60 years old were enrolled in this study, with screening questionnaires to exclude active skin diseases at scalp, such as seborrheic dermatitis, psoriasis, eczema, etc Subjects were divided into two groups according to the results of sensitive scalp self‐assessment, 3S, and 10Q questionnaires as described before . Thirty‐two subjects were Non‐sensitive Scalp (NS) group with 0 score in all questionnaires, while 30 subjects were Sensitive Scalp (SS) group with score higher than 1 in all questionnaires.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 62 healthy women aged between 19 and 60 years old were enrolled in this study, with screening questionnaires to exclude active skin diseases at scalp, such as seborrheic dermatitis, psoriasis, eczema, etc Subjects were divided into two groups according to the results of sensitive scalp self‐assessment, 3S, and 10Q questionnaires as described before . Thirty‐two subjects were Non‐sensitive Scalp (NS) group with 0 score in all questionnaires, while 30 subjects were Sensitive Scalp (SS) group with score higher than 1 in all questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Sensitive scalp, defined as abnormal and unpleasant sensory reactions of the scalp including itching, prickling, tightness, pain, and burning to environmental stimulus, is one of the most sensitive body region reported by consumers, with a high incidence of 44.2% in France and 35.77% in China . Visible signs of inflammation are usually absent in sensitive scalp due to numerous thick hairs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous sensitive scalp studies have been reported in England, the USA, France, and China; in these studies, approximately half of the population of these countries was found to be affected. In particular, the distribution of sensitive scalp was higher in women (60%) …”
Section: Introductionmentioning
confidence: 96%